2015
DOI: 10.4049/jimmunol.1500530
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial RNA: An Underestimated Stimulus for Innate Immune Responses

Abstract: Although DNA of bacterial and viral origin, as well as viral RNA, have been intensively studied as triggers of innate immune responses, the stimulatory properties of bacterial RNA and its role during infections have just begun to be deciphered. Bacterial RNA is a strong inducer of type I IFN and NF-κB–dependent cytokines, and it also can activate the Nlrp3 inflammasome. In this review, we focus on the receptors and signaling pathways involved in innate immune activation by bacterial RNA and analyze the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 83 publications
(124 reference statements)
1
72
0
Order By: Relevance
“…Upon submission of this study, four reports on Gram-positive bacterial RNA sensing by hTLR8 or on mTLR13 structure have been published and largely summarized [26][27][28][29][30]. Thus, S. aureus as well as Streptococcus pyogenes and Streptococcus agalactiae and Listeria monocytogenes total RNAs activate hTLR8 but not TLR7 [26,28].…”
Section: Perspective and Concluding Remarksmentioning
confidence: 98%
“…Upon submission of this study, four reports on Gram-positive bacterial RNA sensing by hTLR8 or on mTLR13 structure have been published and largely summarized [26][27][28][29][30]. Thus, S. aureus as well as Streptococcus pyogenes and Streptococcus agalactiae and Listeria monocytogenes total RNAs activate hTLR8 but not TLR7 [26,28].…”
Section: Perspective and Concluding Remarksmentioning
confidence: 98%
“…For instance, TLR3 has been described to detect rhinovirus, and TLR7 recognizes the RNA‐viruses influenza virus, vesicular stomatitis virus, and Coxsackie B virus . Recent studies have shown that in particular human TLR8 is an important receptor for the detection of various pathogenic bacteria . Borrelia burgdorferi , the causative agent of Lyme disease, is recognized by TLR7 in human pDCs and induces secretion of type I and III IFNs .…”
Section: Role Of Rna‐sensing Tlrs In Detection Of Viruses Bacteria mentioning
confidence: 99%
“…TLR3 recognizes double‐stranded RNA (dsRNA) and utilizes the adaptor molecule TIR domain‐containing adapter‐inducing IFN‐β (TRIF, also known as TICAM1), while signal transduction of TLR7‐9 and TLR13 is dependent on myeloid differentiation primary response 88 (MyD88) . Human TLR7 and TLR8 both recognize single‐stranded RNA (ssRNA) and TLR9 is specific for unmethylated CpG DNA . The most recent identified NA‐sensing TLR is TLR13 which recognizes a specific sequence in bacterial 23S ribosomal RNA (rRNA) .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, pDCs are very nearly the exclusive contributors to IFN secretion from PBMCs, which is why PBMC preparations are popular in measurements of TLR7 stimulation via ELISA-based quantification of IFN in the supernatant after exposure of PBMCs to stimulating agents. In contrast, TLR8 is found in monocytes where stimulation induces TNF (31). While RNA recognition of this system has long been described as specific for ssRNA (2), recent results suggest that this simplified review is in need for some refinement.…”
Section: Introductionmentioning
confidence: 99%